Immunohistochemistry. Issue 9 (14th September 2022) - Loughran, Patricia A.; Ross, Mark A.; St. Croix, Claudette M.
Abstract: Immunohistochemistry is an essential technique for the localization and measurement of proteins in cells and tissues. This article describes methods for labeling proteins in adherent and suspension cell cultures and in tissue sections. Choices of antibodies and detection methods are discussed, and detailed troubleshooting guidelines are provided. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Immunofluorescent labeling of cells grown as adherent monolayers Alternate Protocol 1 : Immunofluorescent labeling of cells in suspension Basic Protocol 2 : Immunofluorescent labeling of tissue sections Alternate Protocol 2 : Immunofluorescent labeling using streptavidin‐biotin conjugates Alternate Protocol 3 : Immunofluorescent double‐labeling of tissue sections Alternate Protocol 4 : Immunofluorescent double‐labeling of tissue sections with two primary antibodies from the same host species